Implementasi Program Manajemen Sampah untuk Peningkatan Kapasitas SDM pada Pedagang di Cifest Cikarang - Citra Anisa Tika Putri; Zulfa Zakiatul Hidayah; Dhonny Suwazan; Maharina Maharina (Lembaga Pengembangan Kinerja Dosen, 2025)
The behavior of littering in tourist attractions is caused by many factors, such as: (1) Lack of socialization from the government, (2) Insufficient cleanliness facilities around the beach. People litter carelessly because the trash bins are located far away, which makes them dispose of waste around the areas where they sit and relax. (3) A dirty environment. The dirty state of the environment also serves as a reason for people to litter. The Community Service activity of the Faculty of Economics and Business, Universitas Pelita Bangsa will be conducted online and offline (hybrid), located at the Cifest Culinary Market, Jalan Cibarusah Raya, Sukaresmi, South Cikarang, Bekasi Regency, West Java, and also via Zoom.